Taxes, credit market 'imperfections' and inter-country differences in the household saving ratio - Erkki Koskela; Matti Virén (Bank of Finland, 1989)
This paper analyzes aggregate household saving under the capital market imperfection, which is characterized by the wedge between the borrowing rate and the lending rate. Under these circumstances the assumption of a representative household is unlikely to hold and consumers are distributed into savers, liquidity-constrained consumers and borrowers depending on the exogenous future labour income. An interest rate wedge is shown to affect saving positively; as for tax rate, while there are some conflicting tendencies, it will likely affect saving negatively mainly via affecting the post-tax interest rate wedge.
URN:NBN:fi:bof-201807301770
Keywords: 330